Synthesis, characterization, and electrochemical, and electrical measurements of novel 4,4 '-isopropylidendioxydiphenyl bridged bis and cofacial bis-metallophthalocyanines (Zn, Co) - ÖZKAYA, ALİ RIZA (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
4,4'-Isopropylidendioxydiphenyl bridged bis-metallophthalocyanines Zn(II) (5) and Co(II) (6) were synthesized from the compound 4,4'-isopropylidendioxydiphthalonitrile (3) and 4,5-bis(hexylthio)phthalonitrile (4). The new cofacial bis-phthalocyanines Zn(II) (7) and Co(II) (8) were synthesized from the corresponding 3 which can be obtained by the reaction of 4,4'-isopropylidendiphenol (1) with 4-nitrophthalonitrile (2). These complexes have been characterized by elemental analysis, UV/Vis, FT-IR, H-1 NMR and MALDI-TOF mass spectroscopies. The electrochemical properties of the complexes were examined by cyclic voltammetry, differential pulse voltammetry and controlled potential coulometry in nonaqueous media. Electrochemical results showed that while there is not any considerable interaction between the two phthalocyanine rings in bisphthalocyanine complexes 5 and 6, the splitting of the molecular orbitals occurs as a result of the strong interaction between the phthalocyanine rings in cofacial complexes 7 and 8. Measurements of capacitance showed a well defined decrease with increasing frequency and an increase with increasing temperature at lower frequencies. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: bisphthalocyanine; cofacial; synthesis; electrochemistry; conductivity; GAS-SENSING PROPERTIES; BINUCLEAR PHTHALOCYANINES; ZINC PHTHALOCYANINES; METAL-FREE; BALL; SPECTROELECTROCHEMISTRY; CLAMSHELL; ELECTROCHROMISM; CONDUCTION; COMPLEXES